DEFENCE MECHANISM OF THE MAIN CHARACTERS IN “WUTHERING HEIGHTS” BY EMILY BRONTE: PSYCHOLOGICAL APPROACH - Golan Hasan (Politeknik Negeri Sriwijaya, 2018)
This research is about defence mechanism of the main characters of Wuthering Heights novel written by Emily Bronte. This research used psychology of literature approach to analyse the characters of intrinsic element of this fiction. It describes and identifies psychology of the main characters; Heathcliff and Catherine, by using the theory of Sigmund Freud (1961) which is divided into three psychic zones id, ego and superego. Thus, this research focuses on the plication of defence mechanism into the main characters of the novel Heathcliff and Catherine which described in the novel. In this research, the author applies qualitative method to analyse the novel and to find out the description of defence mechanism in Heathcliff and Catherine.